ESTUDO BIBLIOMÉTRICO DA PRODUÇÃO ACADÊMICA BRASILEIRA SOBRE GOVERNANÇA PÚBLICA ENTRE 2017 e 2021 (Gestão & Regionalidade, 2024)
This study presents a bibliometric review of the Brazilian academic production related to public governance, from 2017 to 2021. The delimitation of the search on the Capes Periodicals platform used the terms "Governance" and "Public", the first term appearing in the title and the second in any field, being selected only articles written in Portuguese and published in Brazil. The results point to a growing interest in the theme, which may be due to the concern with transparency and smoothness of public administration in Brazil.